At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Para resolver la expresión \((25 \# 36) - (16 \# 9)\) utilizando la operación definida \( a^2 \# b^2 = 2ab - a + b \), sigamos estos pasos:
1. Primero, calculemos \( 25 \# 36 \):
- Identifiquemos \( a \) y \( b \) en la operación: \( a = 25 \) y \( b = 36 \).
- Sustituyamos en la fórmula: \( 25^2 \# 36^2 = 2 \cdot 25 \cdot 36 - 25 + 36 \).
- Realicemos la multiplicación: \( 2 \cdot 25 \cdot 36 = 1800 \).
- Ahora, combinen todo: \( 1800 - 25 + 36 = 1800 - 25 + 36 = 1811 \).
Por lo tanto, el resultado de \( 25 \# 36 \) es 1811.
2. Ahora, calculemos \( 16 \# 9 \):
- Identifiquemos \( a \) y \( b \) en la operación: \( a = 16 \) y \( b = 9 \).
- Sustituyamos en la fórmula: \( 16^2 \# 9^2 = 2 \cdot 16 \cdot 9 - 16 + 9 \).
- Realicemos la multiplicación: \( 2 \cdot 16 \cdot 9 = 288 \).
- Ahora, combinen todo: \( 288 - 16 + 9 = 288 - 16 + 9 = 281 \).
Por lo tanto, el resultado de \( 16 \# 9 \) es 281.
3. Finalmente, sustraigamos los resultados obtenidos:
- \( (25 \# 36) - (16 \# 9) = 1811 - 281 \).
- Realicemos la resta: \( 1811 - 281 = 1530 \).
Por lo tanto, el resultado de [tex]\((25 \# 36) - (16 \# 9)\)[/tex] es 1530.
1. Primero, calculemos \( 25 \# 36 \):
- Identifiquemos \( a \) y \( b \) en la operación: \( a = 25 \) y \( b = 36 \).
- Sustituyamos en la fórmula: \( 25^2 \# 36^2 = 2 \cdot 25 \cdot 36 - 25 + 36 \).
- Realicemos la multiplicación: \( 2 \cdot 25 \cdot 36 = 1800 \).
- Ahora, combinen todo: \( 1800 - 25 + 36 = 1800 - 25 + 36 = 1811 \).
Por lo tanto, el resultado de \( 25 \# 36 \) es 1811.
2. Ahora, calculemos \( 16 \# 9 \):
- Identifiquemos \( a \) y \( b \) en la operación: \( a = 16 \) y \( b = 9 \).
- Sustituyamos en la fórmula: \( 16^2 \# 9^2 = 2 \cdot 16 \cdot 9 - 16 + 9 \).
- Realicemos la multiplicación: \( 2 \cdot 16 \cdot 9 = 288 \).
- Ahora, combinen todo: \( 288 - 16 + 9 = 288 - 16 + 9 = 281 \).
Por lo tanto, el resultado de \( 16 \# 9 \) es 281.
3. Finalmente, sustraigamos los resultados obtenidos:
- \( (25 \# 36) - (16 \# 9) = 1811 - 281 \).
- Realicemos la resta: \( 1811 - 281 = 1530 \).
Por lo tanto, el resultado de [tex]\((25 \# 36) - (16 \# 9)\)[/tex] es 1530.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.